Impact of general anaesthesia in overall and disease-free survival compared to other types of anaesthesia in patients undergoing surgery for cutaneous melanoma: a systematic review and meta-analysis protocol - Bruno Luís de Castro Araujo; Jadivan Leite de Oliveira; Flavia de Miranda Corrêa; Luis Eduardo Santos Fontes; Andreia Cristina de Melo; Luiz Claudio Santos Thuler (BMJ Open)
Introduction Cutaneous melanoma is an aggressive type of skin cancer. Anaesthetic agents may have an impact on the immune response, postoperative neurohumoral response and tumour progression. This systematic review aims to evaluate the impact of general anaesthesia on overall and disease-free survival compared with other types anaesthesia in patients undergoing surgery for cutaneous melanoma.Methods and analysis The review will analyse data from controlled and observational studies of patients undergoing surgery for melanoma under general anaesthesia compared with other types of anaesthesia. The primary outcomes are overall survival and disease-free survival. The secondary outcomes are health-related quality of life, time to tumour progression, distant disease-free survival, time to treatment failure, cancer-specific survival, biochemical recurrence, return of intended oncological therapy, days alive and out of the hospital at 90 days, cost analysis and adverse events. A comprehensive literature search will be performed using the MEDLINE, EMBASE, Cochrane CENTRAL, Web of Science, LILACS and IBECS databases. Grey literature will also be searched. Risk of methodological bias will be assessed using The Cochrane Collaboration’s revised tool for assessing risk of bias in randomised trials (RoB 2.0) and the Newcastle–Ottawa scale. Two reviewers will independently assess the eligibility of studies and risk of bias; a third author will solve discrepancies. One author will perform data extraction and the other will check the process and data. Qualitative analysis will be carried out using all included studies. A meta-analysis using a random-effects model for pooled risk estimates will be carried out for the two main outcomes and for selected secondary outcomes if they conform to previously stated criteria. The GRADE approach will be used to summarise the quality of evidence.Ethics and dissemination Ethics approval is not required as we analyse data from previously reported studies.PROSPERO registration number CRD42018114918.